Silver nanowires for highly reproducible cantilever based AFM-TERS microscopy: towards a universal TERS probe. Issue 16 (11th April 2018) - Walke, Peter; Fujita, Yasuhiko; Peeters, Wannes; Toyouchi, Shuichi; Frederickx, Wout; De Feyter, Steven; Uji-i, Hiroshi
Abstract : Exceptional performance tips for nanoscale optical imaging are produced using silver nanowires attached to commercial AFM cantilevers. Abstract : Tip-enhanced Raman scattering (TERS) microscopy is a unique analytical tool to provide complementary chemical and topographic information of surfaces with nanometric resolution. However, difficulties in reliably producing the necessary metallized scanning probe tips has limited its widespread utilisation, particularly in the case of cantilever-based atomic force microscopy. Attempts to alleviate tip related issues using colloidal or bottom-up engineered tips have so far not reported consistent probes for both Raman and topographic imaging. Here we demonstrate the reproducible fabrication of cantilever-based high-performance TERS probes for both topographic and Raman measurements, based on an approach that utilises noble metal nanowires as the active TERS probe. The tips show 10 times higher TERS contrasts than the most typically used electrochemically-etched tips, and show a reproducibility for TERS greater than 90%, far greater than found with standard methods. We show that TERS can be performed in tapping as well as contact AFM mode, with optical resolutions around or below 15 nm, and with a maximum resolution achieved in tapping-mode of 6 nm. Our work illustrates that superior TERS probes can be produced in a fast and cost-effective manner using simple wet-chemistry methods, leading to reliable and reproducible high-resolution and high-sensitivity TERS, and thus renders the technique applicable for a broad community.